Pegylation of RNA Spiegelmers by a Novel Widely Applicable Two‐Step Process for the Conjugation of Carboxylic Acids to Amino‐Modified Oligonucleotides. Issue 1 (21st May 2020) - Bethge, Lucas; Vonhoff, Stefan
Abstract: The reaction between N ‐hydroxy succinimide (NHS) ester−activated carboxylic acids and amino‐modified nucleic acids is commonly used for the post‐synthetic modification of oligonucleotides. Here, we report a two‐step variation of the method in which the NHS ester is replaced by the corresponding parent carboxylic acid. In the first step, the carboxylic acid is activated with a standard peptide coupling reagent like HBTU in an anhydrous water‐miscible aprotic organic solvent. In the second step, the solution of the activated carboxylic acid is added to the amino‐modified oligonucleotide in water. The method is demonstrated using 40‐kDa polyethylene glycol (PEG) carboxylic acid and biotin as examples. Recycling of the carboxylic acid, which is typically used in molar excess over the nucleic acid, is shown for the conjugation with 40‐kDa PEG carboxylic acid. This conjugation method is generally applicable to the conjugation of carboxylic acids to amino‐modified oligonucleotides, thus enabling the attachment of small to large molecular entities such as dyes, tags, peptides, and other macromolecules. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : General protocol for the conjugation of an amino‐modified oligonucleotide with a carboxylic acid, exemplified for 40‐kDa PEG carboxylic acid Basic Protocol 2 : Biotinylation of an amino‐modified oligonucleotide using the general conjugation protocol Basic Protocol 3 : Recycling of the carboxylic acid component from the conjugation reaction, demonstrated for 40‐kDa PEG carboxylic acid using ultrafiltration Support Protocol 1 : Analytical AEX‐HPLC method used as in‐process control method to monitor the conjugation reaction with 40‐kDa PEG carboxylic acid Support Protocol 2 : Analytical AEX‐HPLC method used as in‐process control method to monitor the conjugation reaction with biotin Support Protocol 3 : Analytical IP‐RP‐HPLC method used as in‐process control method to monitor the conjugation reaction Alternate Protocol : Separation of 40‐kDa PEG carboxylic acid from unreacted and conjugated oligonucleotide by preparative AEX‐HPLC